2022
DOI: 10.2340/actadv.v102.1061
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhidrosis Comorbidities and Treatments: A Register-based Study among 511 Subjects

Abstract: Hyperhidrosis is a dermatological condition that causes psychosocial impairment and has a negative impact on patients’ quality of life. The epidemiology of hyperhidrosis is currently poorly understood. The aim of this study was to analyse comorbidities and treatments in 511 subjects with hyperhidrosis selected from the patient records of Oulu University Hospital. The mean age of patients with local hyperhidrosis was 27.9 years and the majority were female (62.7%). The most common anatomical site of symptoms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…During the coronavirus disease 2019 pandemic, patients reported higher levels of depression compared with the general population [ 12 ]. Heiskanen et al found that depression was a common comorbidity in 511 patients with localized (11.6%) and generalized HH (28.6%) [ 13 ]. Anxiety was found in 12.7% of patients with generalized HH [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…During the coronavirus disease 2019 pandemic, patients reported higher levels of depression compared with the general population [ 12 ]. Heiskanen et al found that depression was a common comorbidity in 511 patients with localized (11.6%) and generalized HH (28.6%) [ 13 ]. Anxiety was found in 12.7% of patients with generalized HH [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Heiskanen et al found that depression was a common comorbidity in 511 patients with localized (11.6%) and generalized HH (28.6%) [ 13 ]. Anxiety was found in 12.7% of patients with generalized HH [ 13 ]. In a sample of 44,484 patients with HH, Klein et al determined that patients had a higher odds of depression and anxiety compared with controls at baseline and follow-up [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations